Diet-Induced Abdominal Obesity, Metabolic Changes, and Atherosclerosis in Hypercholesterolemic Minipigs - Ahmed Ludvigsen Al-Mashhadi; Christian Bo Poulsen; Karin von Wachenfeldt; Anna-Karin Robertson; Jacob Fog Bentzon; Lars Bo Nielsen; Jesper Thygesen; Lars Poulsen Tolbod; Jens Rolighed Larsen; Søren Kragh Moestrup; Björn Frendéus; Brynjulf Mortensen; et al. (Journal of Diabetes Research)
Background. Obesity and metabolic syndrome (MetS) are major risk factors for atherosclerotic diseases; however, a causal link remains elusive. Animal models resembling human MetS and its complications, while important, are scarce. We aimed at developing a porcine model of human MetS. Methods. Forty pigs with familial hypercholesterolemia were fed a high fat + fructose diet for 30 weeks. Metabolic assessments and subcutaneous fat biopsies were obtained at 18 and 30 weeks, and fat distribution was assessed by CT-scans. Postmortem, macrophage density, and phenotype in fat tissues were quantified along with atherosclerotic burden. Results. During the experiment, we observed a >4-fold in body weight, a significant but small increase in fasting glucose (4.1 mmol/L), insulin (3.1 mU/L), triglycerides (0.5 mmol/L), and HDL cholesterol (2.6 mmol/L). Subcutaneous fat correlated with insulin resistance, but intra-abdominal fat correlated inversely with insulin resistance and LDL cholesterol. More inflammatory macrophages were found in visceral versus subcutaneous fat, and inflammation decreased in subcutaneous fat over time. Conclusions. MetS based on human criteria was not achieved. Surprisingly, visceral fat seemed part of a healthier metabolic and inflammatory profile. These results differ from human findings, and further research is needed to understand the relationship between obesity and MetS in porcine models.